D-chiro-inositol, Vitamin D, and Epigallocatechin Gallate Avoid Surgery in Females with Uterine Fibroids: Two Case Reports - Mario Montanino Oliva (European Medical Journal, 2021)
Uterine fibroids (UF) represent the most common benign tumours in females of reproductive age, and can negatively affect fertility. Patients with UFs need to reduce the tumour size with pharmacological treatments or surgically remove the fibroid before using assisted reproductive technology (ART). On the other hand, surgery implies long waiting times before ART to avoid the risk of rupture of the uterus. Long waiting periods are often unacceptable for older individuals who want to undergo ART procedures. Unfortunately, no specific and safe treatment for UFs is currently available. Here the author reports two cases of patients with UFs and associated heavy menstrual bleeding who seek pregnancy through ART. Both underwent a daily treatment with epigallocatechin gallate, vitamin D, vitamin B6, and D-chiro-inositol for 3 months. The patients showed a volume reduction of 73.8% and 68.4%, respectively. This was associated with decreased blood loss (42.1% and 48.7%, respectively). After 3 months from the end of the treatment, both patients underwent ART procedure without the need for surgical intervention.